The Arab Islamic House in Hashemiya Anbar in light of the archaeological excavations (Al-Adab Journal, 2015)
Anbar, one of the deep-rooted cities, the second significant city of pre-Islam Iraq, the city that played an important role in the Arab-Islamic civilizations, it was the first official capital of the Abbasides before Baghdad. Due to the importance of the city, the State Board of Antiquities and Heritage had undertaken excavations there for more than a season, many buildings and artifacts including a golden treasure that comprised a number of coins, were uncovered within the course of excavations as well as another of silver coins in the first and second strata dated to a period among the 5th – 7th H. centuries. The excavations resulted in the demonstration of a series of dwellings those occupied the central, northern and north-eastern parts of the city, these houses were so adjacent to each other where as some had joint walls. The central court yard house was the dominant plan, the other parts of the house flanked by the central court yard in one or two to three sides, building materials were: burnt brick (Farshi) and gypsum as a mortar.